Response of maiden ewes to the ‘ram effect’ is a robust management practice and a candidate selection trait for enhanced reproductive performance in drylands - I. Ben Salem; M. Rouatbi; M. Mlika; T. Getachew; A. Govind; A. Haile; M. Raggem; R. Lahsoumi; M. Rekik (Animal)
Management of reproduction that relies on naturally based solutions is extremely important to counter the negative perception around hormone-based interventions. In Mediterranean latitudes and wider regions of non-tropical drylands, sheep do not normally ovulate during spring but exposure to a ram can induce oestrus and ovulation. This study assesses the response of maiden Barbarine ewes in drylands to the ‘ram effect’ during springtime and estimates the genetic parameters of this response. The study uses a database documenting, for 24 consecutive years, the response of nulliparous 18-month-old ewes when mated after stimulation by the ‘ram effect.’ In addition to the oestrous and fertility database, a pedigree database was also available. Nearly half of the maiden ewes responded to the ‘ram effect,’ while 24% exhibited spontaneous reproductive activity and displayed oestrus during the first 14 days following the introduction of rams. Nearly 5% of females did not exhibit oestrus, and these animals are proposed for early culling. Average annual values of Normalised Difference Vegetation Index (NDVI), reflecting vegetation cover, and the percent of maiden ewes spontaneously cycling were positively correlated (P = 0.006). Interestingly, NDVI was negatively correlated with the percentage of anoestrus females that did not respond to the ‘ram effect’ but exhibited oestrus beyond the hypothetical time frame commonly used to describe it. Average fertility was 82.8% and was significantly affected by mating year, live weight at mating, and the response to the ‘ram effect.’ The highest fertility (88.39%) was for females spontaneously cycling at the time of ram introduction, and the lowest (83.35%) was for females coming into oestrus beyond the time frame for a ram-induced oestrus and ovulation. Heritability from a univariate logit-transformed analysis for fertility was 0.10 and the genetic correlation between fertility and the interval between ram introduction and oestrus was 0.26, suggesting that a shorter interval is associated with higher fertility. Thus, the interval between ram introduction and oestrus is a good candidate for selective breeding for high fertility of maiden ewes in drylands mated out-of-season using the ‘ram effect.’